Recycling of waste RFL (Resorcinol-Formaldehyde Latex) dip solid in natural rubber-based ply skim compound - Bandyopadhyay S; Agrawal S L; Ameta R; Ameta Suresh C; Dasgupta S; Deuri A S; Mukhopadhyay R (Progress in Rubber, Plastics and Recycling Technology, 2007)
DL
Keywords: Resorcinol formaldehyde latex; RFL; Waste recycling